Development of a learning algorithm for convolutional neural networks - Fu, Jiadi (Nanyang Technological University, 2023)
Over the years, deep learning has become one of the most popular topics in computer science. By training artificial neural networks on large datasets, deep learning algorithms can learn to recognize patterns and features in data and use this learning to make intelligent decisions. That is why it has been widely used in linguistics and image processing.